2016
DOI: 10.4103/1119-3077.179286
|View full text |Cite
|
Sign up to set email alerts
|

Surgical inpatient mortality in a Nigerian Tertiary Hospital

Abstract: Trauma and cancer constitute a great deal of health burden in our region. Strong legislation and screenings with timely interventions are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…It also aids in judicious allocation of scarce resources in terms of manpower and equipment. 9 The World Health Organization (WHO) defined POMR as death…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also aids in judicious allocation of scarce resources in terms of manpower and equipment. 9 The World Health Organization (WHO) defined POMR as death…”
Section: Introductionmentioning
confidence: 99%
“…It also aids in judicious allocation of scarce resources in terms of manpower and equipment. 9 The World Health Organization (WHO) defined POMR as death occurring after a surgical and anesthesia procedure at two time periods: the first period is on the day of surgery (including death in operating theater), and the second period either before discharge from hospital or within 30 days of operation. 1 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…This finding is however lower than the global estimate of genitourinary injury at 10%. A 5-year audit of 527 deaths at a teaching hospital in Nigeria showed that trauma was the commonest cause of mortality (41.8%), and urological causes accounted for 6% of mortality[ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This failure is attributable to a multiplicity of health systemrelated, political and systemic challenges including high levels of corruption among the leadership echelon of Nigeria, incessant strikes in the health sector and interprofessional rivalry among the health workers as well as unabating high incidence of kidnapping and insurgency attacks. Previous mortality reports from UPTH were limited either in the time frame or scope especially given the cosmopolitan settlement pattern of Port Harcourt (George et al, 2009;Unachukwu et al, 2008;Ekeke et al, 2016;Onwuchekwa et al, 2008). This study obviates these limitations inherent in the previous local studies and presents the current pattern and trend of mortality at the University of Port Harcourt Teaching Hospital, Port Harcourt, Nigeria.…”
Section: Introductionmentioning
confidence: 86%